Cannabidiol Interacts Significantly with Everolimus—Report of a Patient with Tuberous Sclerosis Complex - Wiemer-Kruel, Adelheid; Stiller, Brigitte; Bast, Thomas (Neuropediatrics, 2019)
A 6.5-year-old female patient with a TSC2 mutation had been given everolimus (EVE) for 3 years for pharmacoresistant focal epilepsy and for life-threatening, severe ventricular dysrhythmia. EVE had been started with daily dose of 0.15 mg/kg/day and was increased up to 0.6 mg/kg/day. Target blood trough levels of around 9 µg/L had been documented. Although EVE therapy revealed no effect on seizure activity, cardiac rhythm normalized completely. Thus, EVE was reduced to a dose of 0.3 mg/kg/day leading to stable blood trough levels of 4 to 5 µg/L. Due to refractory tonic seizures with a frequency of 1 to 4 per day, we initiated cannabidiol (CBD) treatment, raising it to a daily dose of 200 mg. After 6 weeks, the EVE blood trough levels rose to 12.0 µg/L. Although we halved the EVE dose, her EVE blood trough level continued increasing up to 16.0 µg/L.The CBD dose was increased to 500 mg/day (20.4 g/kg/day), but EEG parameters and seizures failed to respond. Serum concentrations of EVE were unstable under the co-medication with CBD. Depending on the CBD dose, they varied between 1.7 and 12.3 µg/L, while EVE was always administered at the same dose.Although never before reported, CBD and EVE appear to interact, due to the metabolic pathway through CYP 450 3A4. Although we detected no side effects in our patient, we strongly recommend drug monitoring using the combination of CBD with EVE to prevent harmful overdosing.
Keywords: TSC; interaction; everolimus; cannabidiol